THE IMPACT OF USING NATIONAL CONTENT IN FOREIGN LANGUAGE CLASSES ON EDUCATIONAL EFFECTIVENESS - Djamolxojayeva Madinaxon Alisher qizi (International Journal of Literature and Language Studies, 2026)
The integration of national content into foreign language instruction has become one of the priority directions for improving the quality of education in multilingual societies. In Uzbekistan, educational reforms emphasize not only the development of foreign language proficiency but also the preservation of national identity, cultural heritage, and moral values among learners. This study investigates the influence of incorporating national content into English language teaching on students' learning outcomes, motivation, intercultural communicative competence, and linguistic achievement. The research is based on a qualitative and analytical methodology that synthesizes pedagogical theories, linguocultural approaches, competency-based education, and recent educational reforms implemented in Uzbekistan. The findings indicate that integrating authentic national materials-including historical events, cultural traditions, literature, customs, folklore, architecture, national holidays, and biographies of prominent Uzbek scholars-significantly enhances students' classroom engagement and learning motivation. Moreover, learners demonstrate improved speaking, reading, writing, and listening performance because familiar cultural contexts reduce cognitive barriers and facilitate meaningful language acquisition. National content also strengthens students' intercultural competence by enabling them to compare their native culture with global cultures while maintaining a strong sense of national identity.